The Nexus Between Teaching and Research: Easier Said Than Done - Marina Nehme (Legal Education Review)
The University of Canberra (the University or UC) has adopted the signature theme of research-led education/teaching (RLE) for its courses and disciplines, as part of its overarching emphasis on ‘preparing professionals professionally’. The aim is to equip both students and staff with the skills to thrive in a complex and changing environment. This paper discusses how the School of Law has implanted this signature theme. It is a process which illustrates the complex nature of the teaching-research nexus and the many different practices that may be considered as RLE. We consider first the justifications for RLE in undergraduate education and the methods, which might be used to emphasise benefits both to academic staff and to the student body. We then look at the various strategies adopted to encourage RLE. We conducted an audit of UC Law academics and report here on their RLE practices.